Teknologi dan Inovasi Pendidikan dalam Islam Teknologi dan Inovasi Pendidikan dalam Perspektif Pendidikan Islam: Penelitian - Mukhlisin Mukhlisin; Hasnida Hasnida (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This paper aims to discuss Technology and Educational Innovation in Islam. The research conducted is a library-based study. Its objective is to seek evidence of the Qur’anic perspective on technology found within the Qur’an itself. This topic is particularly engaging as an academic study within the framework of tafsir ilmi (scientific exegesis), using a thematic exegesis approach (tafsir maudu’i). The study concludes that the Qur’an does, in fact, address technology in several surahs and verses, including: first, Surah Hud verse 37; second, Surah An-Nahl verse 14; and third, Surah Al-Kahf verse 96. The interpretation of these verses was carried out through contextual and historical approaches, while also considering the views of scholars and experts. The findings of this study are expected to provide a deeper understanding of the Qur’anic perspective on technology and innovation, as well as how these views can be applied in the context of modern science.